Biology and predatory potential of lady bird beetle, Coccinella septempunctata (Lin.) on mustard aphid, Lipaphis erysimi (Kalt.) - ABHISHEK PAREEK, M.K. YADAV*, J.I. PATEL and (Indian Phytopathology, 2016)
Biology and predatory potential of Coccinella septempunctata Linnaeus was studied in the laboratory at 23.22 Â± 2.47Â°C and 62.67 Â± 5.84 per cent relative humidity on mustard aphid, Lipaphis erysimi Kalt. The mean fecundity was 582.44 Â± 93.15 eggs per female while pre-oviposition, oviposition, post-oviposition periods, incubation period, hatching percentage, 1st, 2nd, 3rd, and 4th instars, total larval period , pupal period, male and female adult longevity, and sex ratio were 7.92 Â± 2.45, 21.60 Â± 3.39, 7.16 Â± 1.77, 4.40 Â± 0.77 days, 73.30 Â± 5.27%, 3.73 Â± 0.78, 2.80 Â± 0.76, 3.50 Â± 0.78 and 3.63 Â± 0.85, 13.67 Â± 1.77, 6.73 Â± 1.11, 31.33 Â± 3.28 and 37.30 Â± 3.44 days and 1.0 : 1.39, respectively. The length and breadth of egg larva 1st, 2nd, 3rd and 4th instars, pupa, male and female adult were 1.21 Â± 0.03 and 0.52 Â± 0.05, 1.58 Â± 0.16 and 0.49 Â± 0.06, 2.79 Â± 0.11 and 0.80 Â± 0.06, 5.14 Â± 0.48 and 1.38 Â± 0.12 and 7.38 Â± 0.52 and 1.99 Â± 0.23, 5.42 Â± 0.37 and 3.12 Â± 0.33, 6.05 Â± 0.39 and 4.43 Â± 0.26 and 6.95 Â± 0.44 and 5.46 Â± 0.36 mm, respectively. Â The predatory potential of C. septempunctata larva ranged from 31 to 144 with on an average of 69.26 Â± 35.90 mustard aphids per day while, during whole larval period feeding ranged from 278 to 455 with on an average of 363.07 Â± 41.38 aphids. The adult of C. septempunctata consumed 51 to 98 aphids (L. erysimi) in a day with on an average of 69.41 Â± 3.14 aphids. The adult overall consumed 1851 to 2794 aphids with on an average of 2429.83 Â± 262.28 aphids.